Artificial Intelligence Integration in Madrasah Education: The Strategic Role of Principals in Improving Institutional Quality - Asep Sopian; Yuli Supriani; Eko Suncaka; Ani Apiyani; Muslim; Slamet Setiawan (The Nexus Journal of Education, Management, and Entrepreneurship, 2026)
This study aims to analyze the leadership strategies of madrasah principals in integrating Artificial Intelligence (AI) as an effort to enhance educational quality at MA Al-Hidayah Ibun Bandung. Employing a descriptive qualitative approach, the research involved purposively selected informants, including the principal, teachers, and students. Data were collected through observation, semi-structured interviews, and document analysis, and were subsequently analyzed thematically. The findings indicate that the principal’s leadership strategy comprises four main steps: establishing a data-driven quality orientation, encouraging teachers to utilize learning data for continuous evaluation, strengthening teacher collaboration in academic decision-making, and fostering a madrasah culture that gradually and ethically adapts to AI utilization. Although AI integration has not yet taken the form of a fully centralized digital system, it is evident through the reinforcement of data-based practices, the use of simple digital summaries, and the application of evaluation results for remedial, enrichment, and learning improvement. These strategies contribute to increased teacher responsiveness, precise learning interventions, and the strengthening of a quality-oriented madrasah culture. The study emphasizes that successful AI integration in madrasahs heavily depends on the principal’s leadership in developing vision, teacher capacity, collaboration, and technology governance aligned with Islamic educational values.